Respuesta :

   (x-2)(3x-4)
= (x)(3x) + (x)(-4) + (-2)(3x) + (-2)(-4)
= 3x² + (-4x) + (-6x) + 8
= 3x² - 4x - 6x + 8
= 3x² - 10x + 8

I'm not sure so yeah :3
Assuming you want to expand the equation:
Foil the equation (first, outer, inner, last).

First:
x*3x= 3x^2

Outer:
x*-4=-4x

Inner:
-2*3x=-6x

Last:
-2*-4=8

Put it all together and simplify like terms.
3x^2-4x-6x+8
3x^2-10x+8

Final answer: 3x^2-10x+8

If you want root, apply the Zero Product Property.
(x-2)=0
x=2

(3x-4)=0
3x=4
x=4/3

Final answer: x=2, x=4/3